ISU AKSIOLOGI DALAM FILSAFAT ILMU KOMUNIKASI - Muhammad - Yunus (STAI Bumi Silampari, 2020)
This article describe axiologi issue in communication philosophy. The problems that will be answered in this study are: (1)What does the background which rise the debat on netralitiy of science?(2)What argumentation for those who have defferent perspective? (3) How this debat is overcome?. This research find that term of value free in science originate from Helyocentris Theory that finded by Nicolause Coverniccus. This opinion have contradiction with Christian doctrine.This debat proceeds until Enstein and Positivisme philosophy era. Some of the scientist regard that science should be netral because it is an objective activity, conversly some of expert declare that science must be unnetrality. Science should be developed considering morality. The synthesis of these debat are that netrality of science being on justification level only, however science is not netral when it is on methodology and research object choices.